Riparian or phreatophile woodland and shrubland vegetation in the Central Chilean biogeographic region: phytosociological study - Amigo Vázquez, Javier; Flores-Toro, Lorena; Caballero-Serrano, Verónica (Mediterranean Botany, 2019)
The Mediterranean territory in Chile is an extensive area whose natural vegetation has suffered the impact of man-made activities far more severely than anywhere else in the country. Its northernmost section (the Atacama and Coquimbo regions) is characterised by ombroclimates that range from ultra-hyperarid to arid, and by highly irregular river courses with limited spaces for phreatophilic vegetation that have been exploited by humans as fertile farmlands. However, in the river valleys of the Central Chilean biogeographic province, where the ombroclimate is at least semiarid, there may be permanent watercourses that drain from the Andean mountain range towards the Pacific Ocean that contain representations of riparian or phreatophilic vegetation linked to riverbanks or alluvial terraces, in spite of the inevitable human influence. We studied the most conspicuous plant communities with the most highly developed biomass in these riparian environments, namely willow stands dominated by Salix humboldtiana and accompanied by some autochthonous woody species, in order to clarify their floristic composition and their correct ordination within the syntaxonomy of Chilean vegetation. The data collected suggest the existence of a phytosociological association: Otholobio glandulosi-Salicetum humboldtianae ass. nova, as the majority association in the Central Chilean province. Another possible association which replaces this (Baccharido salicifoliae-Myrceugenietum lanceolatae prov.) is also proposed in the transition to a humid ombroclimate and Temperate macrobioclimate. The floristic contents of these Chilean communities are compared with other associations dominated by Salix humboldtiana described for other territories bordering Chile: Argentina, Bolivia and Peru. However, given that they are all located in a Tropical macrobioclimate and their companion flora is therefore clearly different from the flora present in the Chilean communities, we propose the creation of a new phytosociological class to include these syntaxonomically: Mayteno boariae-Salicetea humboldtianae class. nova. This work also ascribes the association Tessario absinthioidis-Baccharidetum marginalis (representing a prior dynamic stage to Otholobio glandulosi-Salicetum humboldtianae) to the class Tessario integrifoliae-Baccharidetea salicifoliae.